Aging affects GABAergic function and calcium homeostasis in the mammalian central clock - Olde Engberink, Anneke H. O.; de Torres Gutiérrez, Pablo; Chiosso, Anna; Das, Ankita; Meijer, Johanna H.; Michel, Stephan (Frontiers in Neuroscience, 2023)
Aging impairs the function of the central circadian clock in mammals, the suprachiasmatic nucleus (SCN), leading to a reduction in the output signal. The weaker timing signal from the SCN results in a decline in rhythm strength in many physiological functions, including sleep-wake patterns. Accumulating evidence suggests that the reduced amplitude of the SCN signal is caused by a decreased synchrony among the SCN neurons. The present study was aimed to investigate the hypothesis that the excitation/inhibition (E/I) balance plays a role in synchronization within the network. Using calcium (Ca2+) imaging, the polarity of Ca2+ transients in response to GABA stimulation in SCN slices of old mice (20-24 months) and young controls was studied. We found that the amount of GABAergic excitation was increased, and that concordantly the E/I balance was higher in SCN slices of old mice when compared to young controls. Moreover, we showed an effect of aging on the baseline intracellular Ca2+ concentration, with higher Ca2+ levels in SCN neurons of old mice, indicating an alteration in Ca2+ homeostasis in the aged SCN. We conclude that the change in GABAergic function, and possibly the Ca2+ homeostasis, in SCN neurons may contribute to the altered synchrony within the aged SCN network.